Plasmodium vivax Cell-Traversal Protein for Ookinetes and Sporozoites: Naturally Acquired Humoral Immune Response and B-Cell Epitope Mapping in Brazilian Amazon Inhabitants - Rodrigues-da-Silva, Rodrigo Nunes; Soares, Isabela Ferreira; Lopez-Camacho, Cesar; Martins da Silva, João Hermínio; Perce-da-Silva, Daiana de Souza; Têva, Antônio; Ramos Franco, Antônia Maria; Pinheiro, Francimeire Gomes; Chaves, Lana Bitencourt; Pratt-Riccio, Lilian Rose; Reyes-Sandoval, Arturo; Banic, Dalma Maria; et al. (Frontiers in Immunology, 2017)
The Cell-Traversal Protein for Ookinetes and Sporozoites (CelTOS), a highly conserved antigen involved in sporozoite motility, plays an important role in the traversal of host cells during the pre-erythrocytic stage of Plasmodium species. Recently, it has been considered an alternative target when designing novel antimalarial vaccines against P. falciparum. However, the potential of P. vivax CelTOS as a vaccine target is yet to be explored. This study evaluated the naturally acquired immune response against a recombinant PvCelTOS (IgG and IgG subclass) in 528 individuals from Brazilian Amazon, as well as the screening of B-cell epitopes in silico and peptide assays to associate the breadth of antibody responses of those individuals with exposition and/or protection correlates. We show that PvCelTOS is naturally immunogenic in Amazon inhabitants with 94 individuals (17.8%) showing specific IgG antibodies against the recombinant protein. Among responders, the IgG reactivity indexes (RI) presented a direct correlation associated to the number of previous malaria episodes (p=0.003; r=0.315) and inversely correlated with the time elapsed from the last malaria episode (p=0.031; r=-0.258). Interestingly, high-responders to PvCelTOS (RI>2) presented higher number of previous malaria episodes, frequency of recent malaria episodes and ratio of cytophilic/non-cytophilic antibodies than low-responders (RI<2) and non-responders (RI<1). Moreover, a high prevalence of the cytophilic antibody IgG1 over all other IgG subclasses (p<0.0001) was observed. B-cell epitope mapping revealed five immunogenic regions in PvCelTOS but no associations between the specific IgG response to peptides and exposure/protection parameters were found. However, the epitope (PvCelTOSI136-E143) was validated as a main linear B-cell epitope, as 92% of IgG responders to PvCelTOS were also responders to this peptide sequence. This study describes for the first time the natural immunogenicity of PvCelTOS in Amazon individuals and identifies immunogenic regions in a full-length protein. The IgG magnitude was mainly composed by cytophilic antibodies (IgG1) and was associated with recent malaria episodes. The data presented in this paper adds further evidence to consider PvCelTOS as a vaccine candidate.